IMPLEMENTASI SISTEM INFORMASI PERON SAWIT BERBASIS MOBILE MENGGUNAKAN METODE SDLC - Oktorina, Fenty Kurnia; Nofiar, Andri (JAMI: Jurnal Ahli Muda Indonesia, 2022)
The process of selling palm fruit is still manual, only relying on the interaction media between the palm oil platform owner and oil palm farmers directly, while the farmers who will sell must come to the palm oil platform, for price information is still known manually only when the sale of palm oil is carried out and data processing unorganized palm oil sales. The solution to this problem is to build a mobile-based palm oil platform information system using the android studio framework with the java language. The purpose of this system is to avoid price monopoly by oil palm platform owners and to offer an information system as a solution for open communication information between oil palm farmers and oil palm platform owners. Furthermore, increasing the competitiveness of open and healthy businesses among palm oil platforms. The expected result is a palm oil platform information system to assist oil palm sales activities in providing information to oil palm farmers and this system can be accessed at any time using the internet network.